Emergency presentations of acute biliary pain: changing patterns of management in a tertiary institute. Issue 12 (9th November 2018) - Cox, Daniel R. A.; Fong, Jonathan; Liew, Chon Hann; Goh, Su Kah; Yeoh, Michael; Fink, Michael A.; Jones, Robert M.; Mukkadayil, Jude; Nikfarjam, Mehrdad; Perini, Marcos V.; Rumler, Greg; Starkey, Graham; et al.
Abstract : Background: Acute biliary pain is the most common presentation of gallstone disease. Untreated patients risk recurrent pain, cholecystitis, obstructive jaundice, pancreatitis and multiple hospital presentations. We examine the outcome of implementing a policy to offer laparoscopic cholecystectomy on index presentation to patients with biliary colic in a tertiary hospital in Australia. Methods: This is a retrospective cohort study of adult patients presenting to the emergency department (ED) with biliary pain during three 12‐month periods. Outcomes in Group A, 3 years prior to policy implementation, were compared with groups 2 and 7 years post implementation (Groups B and C). Primary outcomes were representations to ED, admission rate and time to cholecystectomy. Results: A total of 584 patients presented with biliary colic during the three study periods. Of these, 391 underwent cholecystectomy with three Strasberg Type A bile leaks and no bile duct injuries. The policy increased admission rates (A = 15.8%, B = 62.9%, C = 29.5%, P < 0.001) and surgery on index presentation (A = 12.0%, B = 60.7%, C = 27.4%, P < 0.001). There was a decline in time to cholecystectomy (days) (A = 143, B = 15, C = 31, P < 0.001), post‐operative length of stay (days) (A = 3.6, B = 3.2, C = 2.0, P < 0.05) and representation rates to ED (A = 42.1%, B = 7.1%, C = 19.9%, P < 0.001). There was a decline in policy adherence in the later cohort. Conclusion: Index hospital admission and cholecystectomy for biliary colic decrease patient representations, time to surgery, post‐operative stay and complications of gallstone disease. This study demonstrates the impact of the policy with initial improvement, the dangers of policy attrition and the need for continued reinforcement.